Impacts of Water Quality on Finfish and Shellfish Biodiversity in the River Meghna (Dhaka University Journal of Biological Sciences, 2022)
Fish biodiversity largely depends on different environmental factors including water quality parameters. The current study was conducted to investigate the impacts of water quality variables on fish biodiversity at upstream and downstream of the river Meghna in dry and rainy season in 2011. Twelve water samples and 66 fish samples were collected from 2 different sampling stations of the river Meghna during the study period where 61 were finfish species and 5 were shellfish species. The number of finfish and shellfish catch at upstream in both dry and rainy seasons were significantly higher than that of downstream (p